(untitled) - Mill, John Stuart (New York, 1992)
The book discusses about individual rights and the responsibilities of society. It provides the moral and theoretical justification for liberal democracy and their incalculable influence on modern history testifies not only to the force of their arguments, but also to the power ideas can have over human affairs
Keywords: liberty